Numerical simulation and analysis of early-age thermal crack control in reinforced concrete retaining structures - Mejia, Ralph Jopie T.; Tingatinga, Eric Augustus J. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Early-age thermal cracking in Reinforced Concrete (RC) retaining structures occurs when the tensile strain, arising from restrained thermal contraction exceeds the tensile strain capacity of the concrete. In this paper, a finite element model was implemented to simulate and analyze the early-age behaviour of RC retaining structures. The proposed numerical model incorporates transient thermal effects in the evaluation of thermo mechanical response related to the evaluation of cracks due to the inhomogeneous volume changes associated with temperature rise and differentials caused by exothermic hydration process of concrete. The thermo-mechanical elements were idealized as three-dimensional 20-node solid element in ANSYS that was used to obtain nodal temperature and stress distribution throughout the surface of the retaining wall and its thickness. Extreme temperature variations at an assumed site in Tuguegarao City were used in thermal analyses. Boundary conditions of the model concerning heat flow fundamentals, i.e., conduction, convection, radiation and heat generation, were applied to the model. Basis for comparative assessment of early-age temperature rise and differentials in concrete were developed from Construction Industry and Research Information Association (CIRIA) 660. Results show that the temperature development within the structure obtained using the proposed numerical model agree well with the results from literature. Maximum temperatures and tensile stresses at the interior and exterior surface of the wall were reasonably estimated and cracking pattern were obtained and verified using the crack index. Furthermore, this study confirms that sensitivity among the influencing factors contributing to the early-age cracks such as concrete composition, environmental and technological conditions during casting and curing of concrete should be balanced to control early-age thermal cracking. This study will serve as a basis model for researchers in determining early-age thermal cracks taking into account the simplified and realistic approach in the Philippine-based setting.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Reinforced concrete -- Cracking; Finite element method; ANSYS (Computer system); Concrete -- Thermomechanical properties; Construction Industry Research and Information Association (CIRIA).